Recognizing Women’s Agency: Historical Depictions of Zubaidah bint Ja’far’s Philanthropic Activities and Patronage within the Abbasid Public Sphere - Ulfah, Siti Mariam; Syafitri, Juliani; Hafis, Muhammad (An-Nida', 2025)
This article examines the strategic role of Zubaidah bint Ja’far, the wife of Caliph Harun al-Rashid, in shaping the intellectual and cultural milieu of the Abbasid Dynasty through women’s agency in informal domains, particularly philanthropy and patronage. Employing a historical-analytical methodology, the study analyzes primary sources, including classical Islamic chronicles, alongside secondary literature on patronage, philanthropy, and gender studies within Islamic history. The analysis is informed by Simone de Beauvoir’s existentialist feminism, as articulated in The Second Sex, to interpret the tension between women’s status as the Other within a patriarchal system and Zubaidah’s role as an active agent influencing civilization. The findings indicate that Zubaidah transcended structural constraints through monumental social and religious initiatives, notably the construction of the Darb Zubaidah pilgrimage route—now recognized by UNESCO—and extensive water infrastructure projects. Additionally, her patronage of the arts and sciences, encompassing support for poets, scholars, and the establishment of literary salons, underscores her substantial contribution to the consolidation of the Abbasid intellectual tradition. The study concludes that, despite lacking formal political authority, Zubaidah successfully established enduring social and cultural infrastructures. This research advances Islamic historiography by demonstrating that women’s agency was not peripheral but functioned as a transformative force shaping the course of civilization, thereby opening avenues for further inquiry into women’s roles across historical contexts. Abstrak: Artikel ini menyoroti peran strategis Zubaidah binti Ja’far, istri Khalifah Harun al-Rasyid, dalam membentuk iklim intelektual dan budaya pada masa Dinasti Abbasiyah melalui agensi perempuan dalam ranah non-formal, khususnya filantropi dan patronase. Penelitian ini menggunakan pendekatan historis-analitis dengan menelaah sumber primer berupa kronik klasik Islam dan sumber sekunder terkait patronase, filantropi, serta studi gender dalam sejarah Islam. Analisis didasarkan pada kerangka feminisme eksistensialis Simone de Beauvoir dalam “The Second Sex” untuk menafsirkan kontradiksi posisi perempuan sebagai the “other” di tengah sistem patriarki dengan kapasitas Zubaidah sebagai subjek aktif yang membentuk peradaban. Hasil kajian menunjukkan bahwa Zubaidah melampaui keterbatasan strukturalnya melalui proyek sosial dan keagamaan yang monumental, antara lain pembangunan jalur haji Darb Zubaidah—yang kini diakui UNESCO—serta infrastruktur air berskala luas. Selain itu, perannya sebagai patron seni dan ilmu pengetahuan, termasuk dukungan terhadap penyair, cendekiawan, dan penyelenggaraan majelis sastra, memperlihatkan kontribusi signifikan dalam penguatan tradisi intelektual Abbasiyah. Temuan ini menegaskan bahwa meskipun tidak menempati jabatan formal, Zubaidah mampu menciptakan infrastruktur sosial dan kultural yang berkelanjutan. Penelitian ini berkontribusi pada kajian historiografi Islam dengan menunjukkan bahwa agensi perempuan tidak bersifat marjinal, melainkan dapat menjadi kekuatan transformasional yang menentukan arah peradaban, sekaligus membuka ruang bagi studi lanjutan mengenai peran perempuan lintas periode sejarah.